Evaluasi Website Rakuten Indonesia dengan Eyetracking Usability Testing - Herawati, Yani; Halim, Sandy; Tesavrita, Ceicalia (Jurnal Rekayasa Sistem Industri, 2016)
The increasing internet users in Indonesia has encourage companies to take advantage of internet technology in its business (e-commerce). Amid the growth of e-commerce, Rakuten Indonesia (RI) as one of the e-commerce company, have to compete in order to retain its existence. For e-commerce companies, websiteâs usability has an important role in attracting consumers to conduct transactions. RI websiteâs usability will be evaluated using Eyetracking usability testing. Eyetracking usability testing use the results of the gaze replay, gaze plots, heat maps, and the area of interest (AOI). The evaluation was done for the website features (product categorization, filtering products, sorting products, product description, saving products, as well as ordering the product), and the placement of the advertisement on the homepage RI website. From the evaluation, it was found 10 problems related RI websiteâs feature and the improvements was made. From the results of the evaluation of advertisementâs placements based AOI, can be determined the cost of advertising and the content of the advertisement on a specific area on the websites homepage.